Determinan Keputusan Pembelian Pembersih Wajah Pria Pada Generasi Gen Z - Nafilah Khoirotun Ni'am; Wenti Krisnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the influence of brand image, social media marketing, celebrity endorsement, and E-WOM on the purchasing decisions of Generation Z consumers regarding Kahf facial cleanser products. This quantitative study employs a purposive sampling technique and involves 150 Generation Z university students at Universitas Muhammadiyah Gresik who have used or are currently using Kahf facial cleanser. Data were collected via a 5-point Likert scale questionnaire and analyzed using Partial Least Squares. The study reveals that brand image, social media marketing, and celebrity endorsement positively influence consumer purchasing decisions. However, the E-WOM variable was not found to have a positive impact on customer purchasing decisions. These findings are expected to contribute to the existing literature, particularly regarding Gen Z consumer behavior. Furthermore, they can serve as a reference for companies in formulating more efficient digital marketing strategies to assist consumers in making more rational and well-informed purchasing decisions.